Les trois âges du paysage - Philippe Montillet (Projets de Paysage)
If the links between man and landscapes have always been very strong ; these relationships, on the other hand, have changed a lot in the course of centuries. First of all, the farmer was at the origin of landscapes through farming activities. Then, the artist represented them in his own image - by putting man and his sensibility at the core of the relationship. For a century, a third age of landscape has appeared with landscape architects and engineers. From now on, it is a matter of making the human relationships towards landscapes entering a territorial policy approach - in which numerous actors are concerned. Between the age of the farmers, the one of the artists and the one of the engineers, the article shows that there is a continuity and a logic in the region of Ile-de-France.